Designing a Social Business Model to Empower Persons with Disabilities Through Art Therapy-Based Community Engagement - Muhammad Mukhlis; Dina Dellyana (Community Engagement and Emergence Journal (CEEJ), 2025)
Amisbudi, an art-based initiative under the Our Dream Indonesia Foundation, empowers neurodiverse youth, especially those with autism and Down syndrome, through painting and creative expression. This study addresses the limitations in Amisbudi’s current operations, including its overdependence on a single founder and the absence of a formalized business model. By proposing a Social Business Model Canvas (SBMC) and Social Return on Investment (SROI), this research aims to create a replicable and sustainable framework that enables community engagement, revenue diversification, and measurable social impact. The study adopts a mixed-method approach including stakeholder interviews, surveys, benchmarking, and internal-external analysis. Findings inform a strategic SBMC proposal the impactful data from SROI for Amisbudi, offering pathways for scale, partnership with CSR programs, and volunteer-driven expansion. This thesis contributes to the discourse on inclusive social entrepreneurship in Indonesia, particularly in the domain of art therapy for people with disabilities.